1995
DOI: 10.4319/lo.1995.40.7.1262
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial carbon metabolism in the Amazon River system

Abstract: Bacterial abundance and production and community respiration were measured at several mainstem and tributary stations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
97
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 32 publications
15
97
2
3
Order By: Relevance
“…Las densidades bacterianas encontradas en la columna de agua fueron similares a las de las regiones templadas. Benner et al (1995), Pace and Cole (1996), Posch et al (1997) y Tuomi et al (1997) hallaron abundancias numéricas semejantes y poca variación cuando se estudian sistemas acuáticos muy diversos; algunos de estos trabajos sólo registran diferencias entre aguas oxigenadas y anóxicas. Según Cole et al (1993) y Biddanda et al (2001, la abundancia bacteriana en diferentes ecosistemas acuáticos varía solamente en uno a dos órdenes de magnitud (10 4 a 10 5 células ml -1 ), de manera similar a lo encontrado en este trabajo.…”
Section: Discussionunclassified
“…Las densidades bacterianas encontradas en la columna de agua fueron similares a las de las regiones templadas. Benner et al (1995), Pace and Cole (1996), Posch et al (1997) y Tuomi et al (1997) hallaron abundancias numéricas semejantes y poca variación cuando se estudian sistemas acuáticos muy diversos; algunos de estos trabajos sólo registran diferencias entre aguas oxigenadas y anóxicas. Según Cole et al (1993) y Biddanda et al (2001, la abundancia bacteriana en diferentes ecosistemas acuáticos varía solamente en uno a dos órdenes de magnitud (10 4 a 10 5 células ml -1 ), de manera similar a lo encontrado en este trabajo.…”
Section: Discussionunclassified
“…in contrast, thirteen other relatively unpolluted tropical coastal lagoons in rio de Janeiro state have an average of 3.65 µg chl a l -1 (Farjalla et al, 2001). the observed initial bacterial abundance (3.4 x 10 9 cells l -1 ), biomass (2.4 µm c), and secondary productivity (0.032 µm c h -1 ) are within the range of most tropical freshwater ecosystems (torréton et al, 1994;Benner et al, 1995;lindell & edling, 1996;Anesio et al, 1997;thomaz & esteves, 1997;Bouvy et al, 1998). direct disposal of sewage into imboassica lagoon, although stimulating phytoplankton growth (melo, 2001), has not resulted in higher bacterial abundance, biomass, and secondary productivity than that found in other, less impacted Brazilian tropical coastal lagoons (Farjalla et al, 2001;Farjalla et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Dark respiration and respiratory fractionation of O 2 isotopes-Incubation bottles were filled with water from 3 m depth and incubated (24-96 h) in a thermostat at in situ temperature. In recent studies, Quay et al (1995) and Benner et al (1995) showed that changes in incubation bottle volumes did not influence respiration rate or isotopic fractionation. Thus, in the present study, we used 300-ml BOD bottles, from which duplicate samples were taken for isotopic measurements.…”
Section: O 2 Gross Production-hmentioning
confidence: 99%